Electricity and magnets - Cash, Terry; Taylor, Barbara 1954-.; Chen, Kuo Kang; Bull, Peter 1960- (London Kingfisher Books, 1989)
Describes the discovery of electricity, how it is generated, and the links between electricity and magnetism. Includes instructions for experiments.
Keywords: Electricity -- Juvenile literature; Electricity -- Experiments -- Juvenile literature; Magnets -- Juvenile literature; Magnets -- Experiments -- Juvenile literature